Obesity and motor skills among 4 to 6-year-old children in the united states: nationally-representative surveys - Castetbon Katia; Andreyeva Tatiana (BMC, 2012)
Abstract Background Few population-based studies have assessed relationships between body weight and motor skills in young children. Our objective was to estimate the association between obesity and motor skills at 4 years and 5-6 years of age in the United States. We used repeated cross-sectional assessments of the national sample from the Early Childhood Longitudinal Survey-Birth Cohort (ECLS-B) of preschool 4-year-old children (2005-2006; n = 5 100) and 5-6-year-old kindergarteners (2006-2007; n = 4 700). Height, weight, and fine and gross motor skills were assessed objectively via direct standardized procedures. We used categorical and continuous measures of body weight status, including obesity (Body Mass Index (BMI) ≥ 95th percentile) and BMI z-scores. Multivariate logistic and linear models estimated the association between obesity and gross and fine motor skills in very young children adjusting for individual, social, and economic characteristics and parental involvement. Results The prevalence of obesity was about 15%. The relationship between motor skills and obesity varied across types of skills. For hopping, obese boys and girls had significantly lower scores, 20% lower in obese preschoolers and 10% lower in obese kindergarteners than normal weight counterparts, p < 0.01. Obese girls could jump 1.6-1.7 inches shorter than normal weight peers (p < 0.01). Other gross motor skills and fine motor skills of young children were not consistently related to BMI z-scores and obesity. Conclusions Based on objective assessment of children's motor skills and body weight and a full adjustment for confounding covariates, we find no reduction in overall coordination and fine motor skills in obese young children. Motor skills are adversely associated with childhood obesity only for skills most directly related to body weight.